POTENSI DAN PERSEPSI MASYARAKAT SERTA WISATAWAN TERHADAP PENGEMBANGAN EKOWISATA DI DESA AIK BERIK, LOMBOK TENGAH - Murianto, Murianto (Jurnal Master Pariwisata (JUMPA); Volume 01, Nomor 01, Juli 2014DO - 10.24843/JUMPA.2014.v01.i01.p03)
Aik Berik village has a wide variety of tourist attractions. This research is aimed at identifying potential ecotourism attractions, activities that could be developed in and around the village. In addition, it will investigate perceptions of local communities and tourists concerning the village’s potential development as an ecotourism destination. The supporting data in the research were collected through qualitative observation, in-depth interviews, questionnaires, and documentation. The data were obtained through purposive sampling for the local communities and convenience sampling for the tourists. It was analysed using a descriptive, qualitative method. This analysis has revealed both positive and negative perceptions among local communities and tourists in response to the potential development of ecotourism.